SOSIALISASI DAN DEMONSTRASI PEMBUATAN PUPUK PHOTOSYNTETIC BACTERIA (PSB) SEBAGAI UPAYA PENINGKATAN PRODUKTIVITAS PERTANIAN DI DESA JARAK KULON JOGOROTO - Nurhayati, Wina; Febri Amalia, Ika Kristie; Wahyudiono, Eko; Nandhif, Muhammad Ainun; Roisantosa, Jaya Dulimast; Muslimin, Ihwan (Agros Journal of Agriculture Science, 2024)
The aim of this activity for the community was to provide training on how to make PSB Fertilizer or Photo Synthetic Bacteria, known as liquid organic fertilizer which helped the photosynthetic process in plants. This activity was attended by service partners, namely the GAPOKTAN in Jarak Kulon Village, totaling 24 people.  PSB making training activities were carried out in Jarak Kulon Village, Jogoroto District, Jombang Regency. The implementation methods used included demonstration methods, namely practicing how to make PSBs, discussion and question and answer methods. Based on the activities that had been carried out, we as the KKM group hope that training participants had an understanding of how to make PSB fertilizer and understood how to use PSB for plants, livestock and fish. Apart from having a lot of benefits, PSB fertilizer is also easy to make and cheap, but you can get a lot of results.